Analisis Pengendalian Kualitas Produk Bakso dengan Metode Statistical Process Control (Spc): Studi Kasus UMKM Bakso Mandiri di Sidoarjo - Muhammad Luthfi Khumaidi; Rahmat Dhandy; Sekar Ayu Wulandari; Julia Agustina (Studia : Journal of Humanities and Education Studies, 2026)
Product quality is an important factor in maintaining competitiveness and customer satisfaction. This study aims to identify product defects, analyze production process stability, determine the causes of defects, and propose improvements at Bakso Mandiri SME in Sidoarjo using the Statistical Process Control (SPC) method. Data were collected from 4.000 meatballs through 20 observations and analyzed using check sheets, p-control charts, Pareto diagrams, Ishikawa diagrams, and attribute process performance analysis. The results showed that the dominant defect was texture defects (7%), followed by size defects (5.59%), color defects (5.5%), and shape defects (4.9%). The production process was generally under statistical control, although on observation point for texture defects exceeded the upper control limit. The causes of defects were related to human factors, methods, materials, machines, environment, and measurement. Recommended improvements include consistent implementation of srandard operating procedures (SOPs), stricter raw material supervision, employee training, and continuous application of SPC to reduce product defects and improve product quality.